Long-Term Outcome Following Liver Transplantation for Primary Hepatic Tumors-A Single Centre Observational Study over 40 Years - Christoph Leiskau; Norman Junge; Frauke E. Mutschler; Tobias Laue; Johanna Ohlendorf; Nicolas Richter; Florian W. R. Vondran; Eva-Doreen Pfister; Ulrich Baumann (MDPI AG, 2023)
The incidence of pediatric liver tumors in general has been rising over the last years and so is the number of children undergoing liver transplantation for this indication. To contribute to the ongoing improvement of pre- and post-transplant care, we aim to describe outcome and risk factors in our patient cohort. We have compared characteristics and outcome for patients transplanted for hepatoblastoma to other liver malignancies in our center between 1983 and 2022 and analysed influential factors on tumor recurrence and mortality using nominal logistic regression analysis. Of 39 children (16 f) who had transplants for liver malignancy, 31 were diagnosed with hepatoblastoma. The proportion of malignant tumors in the transplant cohort rose from 1.9% (1983-1992) to 9.1% in the current decade (p < 0.0001). Hepatoblastoma patients were transplanted at a younger age and were more likely to have tumor extent beyond the liver. Post-transplant bile flow impairment requiring intervention was significantly higher compared to our total cohort (48 vs. 24%, p > 0.0001). Hearing loss was a common side effect of ototoxic chemotherapy in hepatoblastoma patients (48%). The most common maintenance immunosuppression were mTor-inhibitors. Risk factors for tumor recurrence in patients with hepatoblastoma were higher AFP before transplant (AFPpre-LTX), a low ratio of AFPmax to AFPpre-LTX and salvage transplantation. Liver malignancies represent a rising number of indications for liver transplantation in childhood. Primary tumor resection can spare a liver transplant with all its long-term complications, but in case of tumor recurrence, transplantation might have inferior outcome. The rate of acute biopsy-proven rejections and biliary complications in comparison to our total transplant cohort needs further investigations.